Analyzing the access of Nepalese Non-financial Firms to the Capital Market and Examining their Approaches to External Financing - Silwal, Prem Prasad (PYC Nepal Journal of Management, 2023)
The purpose of this study is to investigate the funding behavior of investors, whether they lean towards a futuristic or historical approach, in relation to their decisions regarding debt financing. Moreover, it focuses on how financial performance is more sensitive to small constraint firms relative to large unconstraint firms for their potential funding. The stud employed a quantitative approach and an analytical research design to investigate how firm characteristics influence debt financing decisions in Nepalese non-financial firms from 2001 to 2019. Specifically, it employed descriptive and causal-comparative research methodologies to assess its goals. Findings suggest that smaller firms encounter challenges in accessing capital markets, resulting in a diminished impact of tangibility on profitability sensitivity when compared to larger enterprises. As a result, smaller enterprises rely more on internal funding, and their cash reserves are more closely tied to their performance. Notably high Tobin’s Q values indicate that Nepalese managers tend to adopt a forward-looking approach in their leverage decisions. Financing decisions of Nepalese firms appear to be more influenced by capital market considerations, indicating a forward-looking approach. The findings of this study could be useful to the finance managers while they are in a position to employ external financing to their perspective projects.